The Impact of Pre-closing Implementation to Price Efficiency in Indonesia Stock Exchange - Pradityo, Gilang (The Indonesian Capital Market Review, 2014)
Indonesia Stock Exchange has really concerned about improving stock market quality these days. One of the effort is pre-closing trading session implementation. It refers to Decision of the Board of Directors of The Indonesia Stock Exchange Number Kep-00399/BEI/11-2012, regarding Amendment to Rule Number II-A concerning Equity-Type Securities Trading. The rule is effective on 2nd Januar, 2013 and Indonesia Stock Exchange has implemented it since that date. The purposes of pre-closing implementation are to mitigate marking the close, which is the practice of buying security at the very end of the trading day at a significantly higher price than the current price of the security, and to improve market quality. This paper attempts to veryfy whether the impact of pre-closing implementation to price efficiency is positive or not. The result shows that the pre-closing implementation has the positive impact to price efficiency. It reduces the return volatility and market manipulation at the closing time which also means that the pre-closing implementation has effectively improved market quality in Indonesia Stock Exchange.